Oriental Silk = Xiang chou - Zhu, Xiaowen (Hatje Cantz Verlag, 2020)
In Oriental Silk, a multimedia project by Berlin-based Chinese artist and writer Xiaowen Zhu (born 1986), a narrative unfolds on the eponymous company, founded in Los Angeles in the 1970s, focusing on the products, people and places in its history
Keywords: Oriental Silk Co.; Künstlerische Forschung; Seide; Bildband